Literature Review of Financial Performance of Telecommunications Sub Sector Companies Before and During the Covid-19 Pandemic - Yanis Kusniawanti; Sri Suryaningsum; Noto Pamungkas; Dewi Qutrun Nada (Journal of International Conference Proceedings, 2021)
This scientific paper is the first part of a series of research on the impact of the COVID-19 pandemic on the financial performance of telecommunication subsector companies listed on the Indonesia Stock Exchange. This paper describes the current conditions before the covid pandemic and the arguments for the covid pandemic. This paper is important because it will be the basis for further empirical research. The research objects analyzed are profitability ratios, liquidity ratios, leverage ratios, and activity ratios. The results of this literature review show that there is a tendency for differences before the pandemic and during the pandemic. The results of this literature review are the basis for deriving the hypothesis. In further research, the existence of the hypothesis in this paper will be tested empirically.Â  The profitability ratio is suspected to have changed before and during the covid19 pandemic, the liquidity ratio is suspected to have changed before and during the covid-1 pandemic, the leverage ratio is suspected to have changed before and during the covid-1 pandemic, and the activity ratio is suspected to have changed. before and during the covid-19 pandemic.Â